Russian Federation : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2011)
This note focuses on Russia's monetary policy, which is moving toward low and stable inflation. This paper discusses two analytical measures to analyze the monetary policy-core inflation measure and a group of leading indicators model (LIM). The trimmed mean core inflation is a good indicator for analyzing trend inflation and can be used as a viable target for monetary policy. LIMs are widely used for inflation forecasting and are also useful in detecting turning points in inflation.